Réponses

2014-02-17T18:33:36+01:00
A) 5/6 + - 1/3
= 5/6 - 1 x 2 / 3 x 2
= 5/6 - 2/6
= 3/6
= 3 x 1 / 3 x 2
= 1/2

b) 7/9 - 1/-27
= 7 x 3 / 9 x 3 - 1/-27
= 21/27 -1/27
= 20/27

c) -8/5 + 23/50
= -8 x 10 / 5 x10 + 23/50
= -80/50 + 23/50
= -57/50

d) 45/15 - 7/3
= 45/15 - 7 x 5 / 3 x 5
= 45/15 - 35/15
= 10/15
= 5 x 2 / 5 x 3
= 2/3

e) 4/11 + 2
= 4/11 + 2 x 11 / 1 x 11
= 4/11 + 22/11
= 26/11

f) 8/-91 + -1/7
= 8/-91 + -1 x 13 / 7 x 13
= -8/91 - 13/91
= -21/91
= 7 x -3 / 7 x 13
= -3/13

g) 5/2 - - 45/4 + 2/8
= 5 x 4 / 2 x 4 + 45 x 2 /4 x 2 + 2/8
= 20/8 + 90/8 + 2/8
= 112/8
= 8 x 14 / 8 x 1
= 14/1
= 14

h) 4 - 5/-49 + (-8/7)
= 4 x 49 / 1 x 49 - 5/-49 + (-8 x 7 / 7 x 7)
= 196/49 - 5/49 - 56/49
= 135/49
merci beaucoup 1000 merci maudmarine
De rien :)